# Maths Problem

Question asked by AdYrL in #Coffee Room on Jan 13, 2009

AdYrL · Jan 13, 2009

Rank E2 - BEGINNER

Hi all,

If i have a problem of changing:

d^2 (k^1/2)/ dx^2 + d^2(k^1/2)/dx^2 = 0 to

d^2 (phi)/ dx^2 + d^2(phi)/dx^2 = 0

and given that T = k^1/2*phi

How do i change it? Posted in: #Coffee Room

If i have a problem of changing:

d^2 (k^1/2)/ dx^2 + d^2(k^1/2)/dx^2 = 0 to

d^2 (phi)/ dx^2 + d^2(phi)/dx^2 = 0

and given that T = k^1/2*phi

How do i change it? Posted in: #Coffee Room